Generation of a human induced pluripotent stem cell line NTUHi006-A from a polycystic ovarian syndrome patient - Chia-Eng Wu; Hsiang-Po Huang; Hong-Nerng Ho; Mei-Jou Chen (Stem Cell Research)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder related to multifactors and genetic polymorphisms. Here, we derived an induced pluripotent stem cell (hiPSC) line NTUHi006-A from a phenotype A (full-blown) PCOS patients with clinical hyperandrogenism, chronic anovulation, and polycystic ovarian morphology on ultrasonography. NTUHi006-A showed stemness, pluripotency and stem cell-like morphology.